Behaviour of cable-stayed bridge with cable losses - Lim, Dou Xuan (2018)
Progressive collapse have always been a serious threat to cable-stayed bridge, and has historically caused vast demolition of man-made structure and loss of lives. It is a kind of structural failure, which caused by breakdown of a particular structural part and the incapability of the structural system to cope with the disruption of force. A chain reaction will be generated, causing the destruction of the whole bridge structure. In this research, the structural performance of a cable-stayed bridge under cable failure has been studied.This research demonstrate the modelling and analysis of the simplified and modified Penang Second Bridge using SAP2000. This work study the performance of cable-stayed bridge with and without loaded of the static vehicle. This work was also examine the structural response of the cable-stayed bridge to the loss of cables. The progressive collapse analysis has done by removing the cables and checking their effect on the cable axial force.